Desmosomal protein gene mutations in patients with idiopathic dilated cardiomyopathy undergoing cardiac transplantation: a clinicopathological study. Issue 21 (22nd August 2011) - Garcia-Pavia, Pablo; Syrris, Petros; Salas, Clara; Evans, Alison; Mirelis, Jesus G; Cobo-Marcos, Marta; Vilches, Carlos; Bornstein, Belen; Segovia, Javier; Alonso-Pulpon, Luis; Elliott, Perry M
Abstract : Backgroud: Idiopathic dilated cardiomyopathy (DCM) is the most frequent indication for orthotopic heart transplantation. It has been suggested that mutations in genes encoding desmosomal proteins, more typically associated with arrhythmogenic right ventricular cardiomyopathy, are a cause of DCM. Objectives: To determine the frequency of desmosomal protein gene mutations in heart transplant recipients and their families and to examine histopathological characteristics of explanted organs from mutation carriers. Methods: 89 unrelated patients aged 47.9±13.5 years (80% male) transplanted for end-stage DCM underwent genetic screening of five desmosomal genes (PKP2, DSP, DSC2, DSG2 and JUP). The findings were correlated with clinical features and histological characteristics in explanted hearts. Results: Pathogenic mutations were identified in 12 patients (13%). Five additional patients (6%) had genetic variants of unknown significance. The clinical phenotype of patients with pathogenic mutations was indistinguishable from that observed in patients without mutations. Evaluation of 76 relatives from 14 families with sequence variants (11 with pathogenic mutations and three with variants of unknown effect) identified 38 mutation carriers, four of whom had an overt DCM phenotype. Evidence of co-segregation of mutations with DCM phenotype was found in five families. Histological evaluation of explanted hearts did not show any specific features in patients with pathogenic mutations. Conclusions: Mutations in desmosomal genes are frequent in patients with advanced DCM undergoing cardiac transplantation. These findings emphasise the importance of familial evaluation and genetic counselling in patients with end-stage DCM and pose important challenges for current histopathological criteria for arrhythmogenic right ventricular cardiomyopathy.